The Impact of Leadership, Organizational Culture, and Innovative Work Behavior on Employee Performance in Teak MSME Centers in Pasuruan - Sueb; Mukhlis, Imam; Murwani, F Danardana (Jurnal Multidisiplin Madani, 2024)
This research investigates the impact of leadership, organizational culture, and innovative work behavior on employee performance within Teak Micro, Small, and Medium Enterprises (MSMEs) centers in Pasuruan. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews. With a population of 153 employees in Teak MSMEs in Pasuruan, a sample size of 102 is selected using the Slovin technique. Data collection includes surveys and interviews to gather insights into leadership styles, organizational culture dynamics, innovative work behavior, and employee performance indicators. Statistical analyses, including regression models and thematic analysis, are utilized to interpret the data. The findings contribute to understanding the intricate relationship between leadership, organizational culture, innovative work behavior, and employee performance in the context of Teak MSMEs in Pasuruan, offering valuable insights for both academics and practitioners in the field